Illusion theatres of Orhei in the beginning of XX century. History of their construction and the legislation in the field of cinematography - Alla CHASTINA (Dialogica: Revistă de Studii Culturale și Literatură)
Starting in 1910, the illusion theaters and other performance buildings appeared in Bessarabia, which later became quite widespread in all provinces. The National Archive Agency holds some documents on the consideration of the inquiry of the Orhei townspeople Shlema Gurevich and Froim Pagis for permission to open the first cinema in the center of Orhei town at the end of 1910. This cinema worked successfully in that town for about a half of year. However, on May 12, 1911, the so-called normal rules on cinematography No. 688 were adopted, also published in the Bessarabian Provincial Bulletin No. 74 of July 18 (31), 1912. The illusion theater of Pagis and Gurevich did not meet all the new standards. Despite anonymous complaints to the Bessarabian governor, in May 1913 a new illusion theater opened in Orhei, owned by Shlema Tomashin. He was allowed to hold theatrical and concert evenings in his own cinema. The National Archive Agency has preserved the projects and plans of the first illusion theatres in Orhei.